Myocardial disturbances of intermediary metabolism in Barth syndrome - Greenwell, Amanda A.; Tabatabaei Dakhili, Seyed Amirhossein; Ussher, John R. (Frontiers in Cardiovascular Medicine, 2022)
Barth Syndrome (BTHS) is a rare X-linked mitochondrial disorder due to mutations in the gene TAFAZZIN, which leads to immature cardiolipin (CL) remodeling and is characterized by the development of cardiomyopathy. The immature CL remodeling in BTHS results in electron transport chain respiratory defects and destabilization of supercomplexes, thereby impairing ATP production. Thus, BTHS-related cardiomyopathy appears to share metabolic characteristics of the failing heart being an “engine out of fuel”. As CL associates with numerous mitochondrial enzymes involved in ATP production, BTHS is also characterized by several defects in intermediary energy metabolism. Herein we will describe the primary disturbances in intermediary energy metabolism relating to the heart’s major fuel sources, fatty acids, carbohydrates, ketones, and amino acids. In addition, we will interrogate whether these disturbances represent potential metabolic targets for alleviating BTHS-related cardiomyopathy.